Ethnic persistence, assimilation and risk proclivity - Holger Bonin; Amelie Constant; Konstantinos Tatsiramons; Klaus F. Zimmermann (IZA Journal of Migration, 2012)
This paper investigates whether immigrants adapt to the attitudes of the majority population in the host country by focusing on the effect of ethnic persistence and assimilation on individual risk proclivity. Employing information from a unique representative German survey, we find that adaptation to the host country closes the existing immigrant-native gap in risk proclivity by reducing immigrants' risk aversion and explains the systematic variation in the observed risk attitudes across immigrants of different origins. Our analysis of the adaptation behavior of immigrants suggests that acquisition of social norms is an essential factor in the formation of individual attitudes.
Keywords: D1; D81; F22; J15; J16; J31; J62; J82; 330; risk attitudes; ethnic persistence; assimilation; second generation effects; gender; Migranten; Risikopräferenz; Soziale Norm; Ethnische Gruppe; Deutschland